JAMUR DI PERALATAN neonATAL InTenSIve CARe unIT - Ariani Said; Irda Handayani; Nurhayana Sennang (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Fungus is the one of the micro organisms that causes nosocomial infections. Fungal infections are becoming more frequent occurred from the irrational use of broad spectrum antibiotics, steroids, cytostatica drugs, and chronic disease, and malignancy, babies with low birth weight and patients with decreased immunity. Neonatal Intensive Care Unit (NICU) is a room with specialized treatment, care and equipment to treat infants with high risk. The purpose of this study was to know by identification of the fungus species on the instrument at the NICU of dr. Wahidin Sudirohusodo hospital, Makassar at June 2011. The study design was a cross sectional one. The samples are the incubators and the Continuous Positive Airway Pressure (CPAP) at the NICU of dr. Wahidin Sudirohusodo hospital. The sampling was done by rubbing swab on the incubator and CPAP. The identification of the fungus were carried out with lacto phenol cotton blue staining performed at the Central Public Health Laboratory, Makassar. The Streptomyces sp and Penicillium sp were identified at four incubators, Candida sp was identified at one incubator and so was the Aspergillus sp identified; The fungus that identified at the CPAP was only Penicillium sp. Based on this study it can be concluded that Penicillium sp, Streptomyces sp, Aspergillus sp, as well as Candida sp were found at all incubators and only Penicillium sp was found at CPAP.